Analysis of the clinical characteristics of immune checkpoint inhibitor-related hypophysitis - Zhixiao WANG; Yun SHI; Min SUN; Xuqin ZHENG; Tao YANG; Min SHEN (Zhongguo Linchuang Yixue)
ObjectiveTo analyze the clinical characteristics of immune checkpoint inhibitor (ICI)-related hypophysitis. MethodsA retrospective analysis was conducted on patients diagnosed with ICI-related hypophysitis and treated at the Department of Endocrinology, The First Affiliated Hospital with Nanjing Medical University, between January 2020 and March 2025. Clinical manifestations and prognosis of patients were analyzed. ResultsEleven patients with ICI-related hypophysitis were included. The average age was (62.27±7.63) years, and 9 patients (81.82%) were male. The median time to onset was 9.1 months, and the median number of treatment cycles received was 5. The primary initial symptoms were fatigue and anorexia. Hyponatremia was present in 3 patients (27.27%). Evaluation of anterior pituitary function revealed adrenocorticotropic hormone deficiency as the most common manifestation (90.91%, 10/11), followed by hyperprolactinemia (81.82%, 9/11). Posterior pituitary function remained normal in all patients. Pituitary magnetic resonance imaging showed no abnormality in 4 patients (44.44%). Thyroid dysfunction was observed in 6 patients (54.55%), one of whom (9.09%) also exhibited pancreatic endocrine dysfunction. The average follow-up duration was 36.5 months. Eight patients (72.73%) were alive at the last follow-up. None of the patients recovered their pituitary hormone function. ConclusionsEndocrine adverse events induced by ICIs can involve multiple glandular systems. Clinicians should be highly vigilant for the possibility of ICI-induced hypophysitis in patients receiving ICIs who present with symptoms such as fatigue, anorexia, and hyponatremia.